Characterization of the Adherence of Clostridium difficile Spores: The Integrity of the Outermost Layer Affects Adherence Properties of Spores of the Epidemic Strain R20291 to Components of the Intestinal Mucosa - Mora-Uribe, Paola; Miranda-Cárdenas, Camila; Castro-Córdova, Pablo; Gil, Fernando; Calderón, Iván; Fuentes, Juan A.; Rodas, Paula I.; Banawas, Saeed; Sarker, Mahfuzur R.; Paredes-Sabja, Daniel (Frontiers in Cellular and Infection Microbiology, 2016)
Clostridium difficile is the causative agent of the most frequently reported nosocomial diarrhea worldwide. The high incidence of recurrent infection is the main clinical challenge of C. difficile infections (CDI). Formation of C. difficile spores of the epidemic strain R20291 has been shown to be essential for recurrent infection and transmission of the disease in a mouse model. However, the underlying mechanisms of how these spores persist in the colonic environment remains unclear. In this work, we characterized the adherence properties of epidemic R20291 spores to components of the intestinal mucosa, and we assessed the role of the exosporium integrity in the adherence properties by using cdeC mutant spores with a defective exosporium layer. Our results showed that spores and vegetative cells of the epidemic R20291 strain adhered at high levels to monolayers of Caco-2 cells and mucin. Transmission electron micrographs of Caco-2 cells demonstrated that the hair-like projections on the surface of R20291 spores are in close proximity with the plasma membrane and microvilli of undifferentiated and differentiated monolayers of Caco-2 cells. Competitive-binding assay in differentiated Caco-2 cells suggests that spore-adherence is mediated by specific binding sites. By using spores of a cdeC mutant we demonstrated that the integrity of the exosporium layer determines the affinity of adherence of C. difficile spores to Caco-2 cells and mucin. Binding of fibronectin and vitronectin to the spore surface was concentration-dependent, and depending on the concentration, spore-adherence to Caco-2 cells was enhanced. In the presence of an aberrantly-assembled exosporium (cdeC spores), binding of fibronectin, but not vitronectin, was increased. Notably, independent of the exosporium integrity, only a fraction of the spores had fibronectin and vitronectin molecules binding to their surface. Collectively, these results demonstrate that the integrity of the exosporium layer of strain R20291 contributes to selective spore adherence to components of the intestinal mucosa.